Mentoring Program for Early Childhood Education: A Community-Based Intervention at Himawari Learning Center - Istikomah; Qisthi Fariyani; Susilawati; Jasuri; Niswatul Fauziah (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
This community service program implemented a science play activities mentoring initiative at Himawari Early Childhood Education Center (TPA-KB-TK Himawari) in Semarang, Indonesia. The program aimed to introduce basic science concepts to young children through enjoyable play-based activities while providing parental education on supporting science learning at home. The intervention involved 30 participants including children, parents, and educators. The program utilized simple, safe materials for hands-on experiments such as color mixing, light refraction with CDs, and creating mini lava lamps. Results demonstrated high engagement from children and positive responses from parents regarding the importance of early science introduction. The initiative successfully bridged the gap between theoretical knowledge and practical application in early childhood science education while strengthening university-community partnerships. This program contributes to community development by enhancing educational quality and promoting scientific literacy from an early age.